2007
DOI: 10.1074/jbc.m608542200
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Sheds Syndecan-1 Ectodomains through ZmpC, a Metalloproteinase Virulence Factor

Abstract: Several microbial pathogens stimulate the ectodomain shedding of host cell surface proteins to promote their pathogenesis. We reported previously that Pseudomonas aeruginosa and Staphylococcus aureus activate the ectodomain shedding of syndecan-1 and that syndecan-1 shedding promotes P. aeruginosa pathogenesis in mouse models of lung and burned skin infections. However, it remains to be determined whether activation of syndecan-1 shedding is a virulence mechanism broadly used by pathogens. Here we show that St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 46 publications
1
69
0
Order By: Relevance
“…Previous studies have shown that long linear negatively charged chains of sulfated and nonsulfated disaccharides designated GAGs are increased in CF (44 -46) and lung epithelial shedding of GAG proteoglycans can be stimulated by pathogenic virulence factors (47)(48)(49). In the present study, we hypothesized that LL-37 interacts with GAGs within the CF lung milieu.…”
Section: Ll-37 Is Inactivated and The Peptide Impervious To Proteolytmentioning
confidence: 87%
“…Previous studies have shown that long linear negatively charged chains of sulfated and nonsulfated disaccharides designated GAGs are increased in CF (44 -46) and lung epithelial shedding of GAG proteoglycans can be stimulated by pathogenic virulence factors (47)(48)(49). In the present study, we hypothesized that LL-37 interacts with GAGs within the CF lung milieu.…”
Section: Ll-37 Is Inactivated and The Peptide Impervious To Proteolytmentioning
confidence: 87%
“…The best characterized of them is IgA1 protease, which is involved in pneumococcal adherence and colonization, and it could elicit significant protection against fatal pneumococcal pneumonia in mice (2,37). ZmpC has the capacity to cleave human matrix metalloproteinase-9 (MMP-9) and to stimulate syndecan-1 shedding (12,30), while the role of ZmpD in pneumococcal infection still is unknown. Unlike ZmpC and ZmpD in some pneumococcal strains, ZmpB is ubiquitous in all strains of S. pneumoniae and contributes to the virulence of this pathogen (13).…”
Section: Discussionmentioning
confidence: 99%
“…Syndecan-1 is shed by metalloproteinases 16,[32][33][34][35] and, to block its release, WT mice were injected intraperitoneally with GM6001, a broad-acting metalloproteinase inhibitor, or vehicle at 24 hours after LPS. GM6001 was administered in a delayed manner because pretreatment or early administration of GM6001 has been shown to be protective in mouse models of endotoxemia, in part, by inhibiting TACE (ADAM17)-mediated release of TNF␣.…”
Section: Syndecan-1 Shedding Facilitates the Removal Of Kc And Mip-2 mentioning
confidence: 99%